The Influence of Financial Education, Financial Attitudes, and Lifestyle on The Financial Behavior of E-Commerce Users in Yogyakarta, with Financial Literacy and Self-Control as Moderating Variables - Diah Wulandari; Nur Rahmah Tri Utami (International Journal of Social Service and Research, 2026)
The development of e-commerce has encouraged significant changes in people’s financial behavior, particularly in online consumption activities, which often lead to impulsive spending and unwise financial decision-making. This study aims to analyze the influence of financial education, financial attitude, and lifestyle on the financial behavior of e-commerce users in Yogyakarta and to examine the roles of financial literacy and self-control as moderating variables. This research employed a quantitative approach using a survey method involving 313 e-commerce users in Yogyakarta. The data were analyzed using multiple linear regression and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 25. The results showed that financial education, financial attitude, and lifestyle had positive and significant effects on financial behavior. Financial literacy moderated the influence of financial attitude on financial behavior, while self-control did not moderate the influence of lifestyle on financial behavior. The findings indicate that improving financial education and literacy is essential to encourage wiser financial behavior among e-commerce users. In conclusion, financial education and positive financial attitudes play crucial roles in shaping better financial behavior, whereas lifestyle, when balanced with financial management skills, does not necessarily lead to negative consumption patterns. This study highlights the importance of improving financial education and literacy to promote wiser financial behavior in the use of e-commerce.